Optimization of Surface Roughness of Brass by Burnishing (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Abstract—Cylindrical components are important inseveral industrial applications. The surface quality plays a role in part performance. Non-ferrous surfaces are difficultto-finishduetoseveralissuesencounteredingrindingthatisoptimumfor ferrous metals. Burnishing process, as a metaldeformation process, is believed to be more suitable since iteliminates sticking, wheel dulling and overheating. Themain objective of this work is to optimize the burnishingprocess that can be used to finish the surface of machinedparts. To achieve this, burnishing tool was designed andconstructed in such a way that it can be simply mounted orfixed onto the tool holder of the CNC lathe machine.Experiments are made according to the response surfacemethodology (RSM), in order to improve the reliability ofresults and to reduce the size of the experimental planwithout loss of accuracy. In this work, four burnishingparameters, namely, burnishing speed, feed, depth ofpenetration and number of passes were selected in order tostudy their effects on the surface roughness. Mathematicalmodels, which depend basically on the utilized experimentaldesign, have been developed. Variance of analysis wasconducted to determine the prominent parameters and theadequacy of the models. The results showed that goodsurface roughness can be obtained with minimum cost bytransferring the CNC lathe machine from machine tool tosuper-finishing machine using the proposed burnishing tool.From an initial average roughness of about Ra (4-5 µm), thespecimen could be finished to average roughness of 0.09 µm.